Neonatal Crohn’s disease with Oral ulcer as the first symptom caused by a compound heterozygote mutation in IL-10RA: a case report - Lv, Hongyan; Qiao, Baojun; Fang, Liyuan; Yang, Lihong; Wang, Qiuli; Wu, Sujing; Ren, Pengshun; Li, Lianxiang (Hereditas, 2019)
To investigate the clinical and genetic characteristics of neonatal Crohn's disease (CD), improve recognition of neonatal CD, and reduce the number of patients that are missed or misdiagnosed. A 10-day-old Chinese girl with oral ulcers was admitted to the Department of Neonatology. She later developed a rash and perianal disease, but without diarrhea and stool abnormalities. The patient and her parents underwent next-generation sequencing The results showed that the patient carries a compound heterozygous mutation in the interleukin-10 receptor A (IL-10RA) (NM_001558.3) gene. One heterozygous mutation was c.301 c > T, P. (Arg 101 Trp) in exon 3 of IL-10RA (a missense mutation), and the other was c. 537G > A, P. (Thr 179 =) in exon 4 of IL 10RA (a synonymous mutation). The patient's father also carries the c.301 c > T, P. (Arg 101 Trp) heterozygous mutation in exon 3 of IL-10RA, whereas her mother carries the c.537G > A, P. (Thr 179 =) heterozygous mutation in exon 4 of IL-10RA. The results show that a compound heterozygous mutation in IL-10RA is associated with neonatal CD. Oral ulcers with a rash and perianal disease may be an early symptom of neonatal CD; therefore, such patients should undergo genetic identification as soon as possible.